Posterior epidural disc herniation at L3-L4 mimicking a spinal tumor: a case report - (:unkn) unknown (EDIZIONI MINERVA MEDICA, 2010)
Posterior epidural disc migration is a rare event. Many differential diagnoses are possible in the posterior epidural space other than disc disease. This is a case report of L3-L4 posterior epidural disc herniation that was misdiagnosed as a tumor depending on the pre-operative magnetic resonance imaging study with a peripheral ring enhancement around the mass lesion after IV gadolinium. Decompressive L4 laminectomy was performed and a free disc fragment was observed beneath the lamina. There was neither dural tear nor attachment to it. The patient was free of pain postoperatively. After 3 months, the patient applied to the outpatient clinic for a regular control. The patient was neurologically intact and free of pain. Diagnosis of posterior migrated disc fragment with subtle clinical findings, even though the free fragment has to pass through many anatomical barriers including the nevre roots, is a clinical challenge. Many differential diagnoses should be kept in mind. MRI findings (especially with contrast material use) are useful which should be imprinted with clinical knowledge.
Keywords: Spine; Disc; Spinal neoplasms; MIGRATION; FRAGMENT; MRI